AN INTERACTIVE WEB-BASED EDUCATIONAL APPLICATION FOR PRESERVING TRADITIONAL MALAY DELI MUSICAL INSTRUMENTS: A LUTHER METHOD APPROACH - Muhammad Yoris Gustiawan; Yunita Sari Siregar (Jurnal Kecerdasan Buatan dan Teknologi Informasi, 2026)
The rapid advancement of information technology has significantly influenced the development of learning media in education, creating opportunities for more interactive and flexible learning experiences. However, traditional Malay Deli musical instruments are becoming less familiar among elementary school students due to the dominance of modern musical instruments and limited engaging learning resources. This study aims to design and develop an application-based learning media to introduce traditional Malay Deli musical instruments using the Luther multimedia development method. The application was developed using Construct 2 to create interactive game-based learning content and integrated into a web-based platform using the Laravel framework to ensure accessibility and efficient content management. The research employed a research and development approach following six stages of the Luther method: concept, design, material collection, assembly, testing, and distribution. The developed application features interactive learning materials, audio-visual content, and quiz-based games designed to enhance student engagement and motivation. In addition, an administrative dashboard was implemented to allow teachers to manage learning materials, question banks, and student quiz results dynamically. The results indicate that the developed learning media provides an effective, user-friendly, and engaging learning environment for elementary school students. The integration of multimedia elements supports diverse learning styles and encourages independent learning, while the web-based implementation allows flexible access anytime and anywhere. This study concludes that application-based multimedia learning media can serve as an effective educational tool and contribute to the preservation of traditional Malay Deli cultural heritage by presenting traditional musical instruments in a modern and interactive digital format.